TELOMERIC FUSIONS IN A WILMS-TUMOR - Fettconte, A. C.; Liedtke, H.; Chaves, H.; Thome, J. A.; Tajara, E. H. (Elsevier B.V., 1993)
The present report describes the karyotypic findings in cells from a Wilms' tumor. The most consistent cytogenetic abnormalities detected consisted of translocations involving break and fusion of chromosomal telomeres and telomeric associations frequently affecting the terminus of the short arms of chromosomes 14 and 17.